Evidence of no protection for a recurrent case of pathogen specific clinical mastitis from a previous case. Issue 1 (16th November 2015) - Cha, Elva; Hertl, Julia; Schukken, Ynte; Tauer, Loren; Welcome, Frank; Gröhn, Yrjö
Abstract : The objective of this study was to determine whether the occurrence of a previous case of pathogen-specific clinical mastitis (CM) protects Holstein dairy cows against a recurrent case. Pathogens studied were Escherichia coli, Staphylococcus aureus, Staphylococcus spp., Streptococcus spp., Klebsiella spp., and Trueperella pyogenes . A total of 40 864 lactations (17 265 primiparous and 23 599 multiparous) from 19 835 cows from 5 large, high milk producing New York State dairy herds were analysed. We estimated the effects of parity, calving diseases, milk yield, current season and number of CM cases in the previous lactation on the risk of a first CM case using generalised linear mixed models with a log link and Poisson error distribution. The aforementioned risk factors and the occurrence of previous cases of pathogen-specific CM within the current lactation were evaluated as risks for second and third cases of pathogen-specific CM. Cows with more CM cases in the previous lactation were at greater risk of pathogen-specific CM in the current lactation. Multiparous cows were at greater risk of a second CM case if they had suffered from a first CM case that was caused by the same pathogen as the second case. In contrast, a second CM case generally put cows at greater risk of a third case, irrespective of whether the third case was caused by the same or a different pathogen. Our results showed that a previous case of pathogen specific CM does not generally protect against a recurrent case.